DISEÑO DE UN MANUAL ADMINISTRATIVO - FINANCIERO PARA LA CREACIÓN Y FUNCIONAMIENTO DE LAS CAJAS DE AHORRO COMUNITARIAS - Lanche Calva, Leidy Ximena (2019)
This research proposes an administrative-financial manual for the creation and operation of community savings banks, which contains five sections: implementation, organization, legal framework, procedures and operation. The purpose of this manual is to generate greater efficiency in carrying out activities, to optimize time and resources, in order to provide a quality service for its members. The methodology used was a descriptive-analytical one that allowed for the compilation and substantiation of administrative and financial aspects necessary for its development. Additionally, it is complemented with interviews conducted with the directors of financial organizations of the Popular and Solidarity Economy (EPS) of the rural parishes of the Loja canton, which allowed to establish inefficiencies in the areas: administrative, operative and accounting of the community savings banks. Therefore, the main finding was that the community savings banks must structure the organizational, administrative and operational processes in order to guarantee their sustainability. As a result, a manual was produced under the guidelines established by the Superintendence of Popular and Solidarity Economy, adapting to the needs of its directors and members in general. In addition, the results obtained when compared with other manuals generally show that the institutions of the popular and solidarity financial sector, specifically the community savings banks, must operate under the guidelines established in the manuals: functions, credit and accounting. The manual will provide these financial institutions with the necessary instruments to optimize their administrative and financial management, reduce risks, use of resources, thus achieving stability and improve the economy of the members, through the financing obtained by their savings.